Antimicrobial and Anticancer Activities of Ethyl Acetate Extract of Co-culture of Streptomyces sp. ANAM-5 and AIAH-10 Isolated From Mangrove Forest of Sundarbans, Bangladesh - Md. Uzzal Haque, Md. Ajijur Rahman, Md. Anwarul Haque, Ashish Kumar Sarker, Md. Anwar Ul Islam (Journal of Applied Pharmaceutical Science, 2016)
In this study we investigated the antimicrobial and anticancer activities of ethyl acetate extract of co-culture of Streptomyces sp. ANAM-5 and AIAH-10 isolated from soil of mangrove forest Sundarbans, Bangladesh. The antimicrobial activity of ethyl acetate extract was determined using broth-dilution method against Candida albicans, Saccharromyces cerevaceae and Aspergillus niger whereas anticancer activity was evaluated against Ehrlich Ascites Carcinoma (EAC) cells in Swiss albino mice with the dose of 50 mg/kg and 100 mg/kg body weight (i.p). The Minimum Inhibitory Concentrations (MIC) of ethyl acetate extract was found 32μg/ml against Candida albicans while 64 μg/ml against Saccharromyces cerevaceae and Aspergillus niger. The antineoplastic activity of the crude extract was increased in dose dependent manner with a significant value (p
Keywords: Mixed fermentation, Streptomyces sp., MIC, MFC, anticancer activity.